2012 IEEE PES Innovative Smart Grid Technologies (ISGT) 2012
DOI: 10.1109/isgt.2012.6175769
|View full text |Cite
|
Sign up to set email alerts
|

Simulation models for evaluation of network design and hierarchical transactive control mechanisms in Smart Grids

Abstract: Smart-grid technologies seek to enhance the electri cal grid's efficiency by introducing bi-directional communication and dynamic adaptive control between energy suppliers and consumers. We develop a large-scale network simulation model for evaluating such a hierarchical transactive control system that is part of our work on the Pacific Northwest Smart Grid Demonstration Project. The transactive control system communicates local supply conditions using incentive signals and load adjustment responses using feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A large-scale network simulation model is developed in [14] for the hierarchical transactive control system evaluation. The proposed network simulation model illustrates how transactive control can be used to manage the distribution problem of peak demand, and improve system efficiency and reliability at a large scale.…”
Section: Pilot Projects With Transactive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale network simulation model is developed in [14] for the hierarchical transactive control system evaluation. The proposed network simulation model illustrates how transactive control can be used to manage the distribution problem of peak demand, and improve system efficiency and reliability at a large scale.…”
Section: Pilot Projects With Transactive Controlmentioning
confidence: 99%
“…3. Two-level transactive control system architecture [14] Besides, the costs and benefits of renewables for all market participants using the GridWise transactive energy framework [3] are classified in [15]. Reference [16] reports on the preliminary findings of a residential demand response demonstration that uses the bidding transactions of supply and end-use air conditioning resources communicating with a real-time market to balance the various needs of the participants on a distribution feeder.…”
Section: Pilot Projects With Transactive Controlmentioning
confidence: 99%
“…These strategies typically use either direct control via set-point variation [2], [6] or probabilistic switching-based distributed control [4]. Another stream of recent work employs market-based coordination strategies or a so-called transactive energy control framework to manage the aggregate demand of a large number of electric loads [7]- [13]. Risks related to load synchronization and cold load pick up are discussed in [14]- [16] in the context of direct load control, but there has been limited work to investigate such risks under market coordination strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Transactive control (TC) demonstration projects have shown that with residential loads market-based coordination strategies can reduce utility demand and congestion at peak times [7], [8], [10], [11]. An optimization problem has been formulated in [10] where the coordinator first makes control decisions to maximize the social welfare, and then the individual users choose energy consumption to maximize individual utility based on the coordinator's control decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation